Disaster Communication in Reducing the Impact of Regional Losses in Bengkulu City by Local Government - Lisa Adhrianti; Alfarabi Alfarabi (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
The purpose of this research is to find out and explain the forms of communication that are considered effective and efficient by the Bengkulu regional government in the context of overcoming the impact of losses due to this specific disaster. This research uses a post-positivistic paradigm with a case study research method to find out and evaluate the role of the Bengkulu Regional Government in reducing the impact of losses due to disasters. Data collection will be carried out through interviews and FGDs. The results of the study show that disaster communication in reducing the impact of regional losses is carried out effectively through four aspects, namely: (1) Customer Focus, through efforts to build disaster-related information needed by the community through a flow mechanism for delivering disaster information, starting from the Meteorology, Climatology and Geophysics Agency (BMKG) info to the Regional Disaster Mitigation Agency (BPBD) and passed on to emergency operation center  (Pusdalops) and the media; (2) Leadership Commitment, through the efforts of leaders who are enthusiastic enough to lead disaster resolution in accordance with their main tasks and functions of disasters. In addition, BPBD Leadership elements always go directly to disaster-affected areas; (3) Situational Awareness, through effective communication based on disaster research conducted   independently to  the results of handling and regional operations (disaster exposure area); (4) Media Partnership, through the involvement of the media in the form of collaborative disaster management such as with state-owned radio station RRI Bengkulu, in addition to using social media accounts such as Instagram and holding press conferences during disasters.